A risk score for predicting pulmonary hypertension in patients with non-transfusion-dependent thalassemia in northeastern Thailand: The E-SAAN score. Issue 7 (August 2015) - Teawtrakul, Nattiya; Pussadhamma, Burabha; Ungprasert, Phuangpaka; Prayalaw, Patcharawadee; Fucharoen, Supan; Jetsrisuparb, Arunee; Pongudom, Saranya; Sirijerachai, Chittima; Chansung, Kanchana; Wanitpongpun, Chinadol; Thongbuaban, Srisuda; Thinkhamrop, Bandit; et al.
Abstract : Introduction: Pulmonary hypertension (PH) is a major complication in patients with non-transfusion-dependent thalassemia (NTDT). The risk score was developed to be a screening test for PH risk in these patients. Methods: A multi-center study was conducted in patients with NTDT aged ≥10 years old. PH risk was defined as tricuspid regurgitation velocity >2.9 m/s by echocardiography. The clinical parameters significantly associated with PH were entered into the logistic regression model. Results: The E-SAAN score included (1) age >35 years (2.5 points), (2) time after splenectomy >5 years (2.5 points), and (3) β-thalassemia/hemoglobin E (2 points). Using the cut-off point of 4.5 points, the score showed a good discrimination in the validating group with an area under receiver-operating characteristics curve of 0.88 (95% CI 0.8–0.95). Conclusion: The E-SAAN score is a simple and practical score which can be used as a screening test for PH risk in patients with NTDT.